Statistical shape modelling to analyse the talus in paediatric clubfoot. (August 2021) - Feng, Yixuan; Bishop, Aaron; Farley, Daniel; Mitchell, Joseph; Noonan, Kenneth; Qian, Xiaoping; Ploeg, Heidi-Lynn
One fifth of idiopathic clubfoot deformities cannot be fully corrected by Serial Ponseti casting and deformity recurs in 20%–30% of cases. To avoid x-ray exposure, the joints with largely unossified bones are diagnosed with magnetic resonance images (MRI). Typically, geometric measurements are made in the MRI planes; however, this method is inaccurate compared to measurements on three-dimensional (3D) models of the joint. More accurate measurements using the 3D bone shapes may be better at identifying differences between groups; and therefore, improve diagnosis. The entire set of shape features from MRI can be analysed simultaneously through statistical shape modelling (SSM) which assesses bone morphology of clubfoot in a more sensitive way. A method for SSM of the talus is developed in this study and the shape of the normal talus is compared with the one in clubfeet with residual deformity through both geometric measurements and SSM. Significant differences between two groups were found by both methods; and therefore, might contribute to improve diagnosis of clubfoot.